2016
DOI: 10.1007/s11999-015-4510-8
|View full text |Cite
|
Sign up to set email alerts
|

Global Rating Scales and Motion Analysis Are Valid Proficiency Metrics in Virtual and Benchtop Knee Arthroscopy Simulators

Abstract: Background Work-hour restrictions and fatigue management strategies in surgical training programs continue to evolve in an effort to improve the learning environment and promote safer patient care. In response, training programs must reevaluate how various teaching modalities such as simulation can augment the development of surgical competence in trainees. For surgical simulators to be most useful, it is important to determine whether surgical proficiency can be reliably differentiated using them. To our know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…[43][44][45][46] It is in this area of transferability that supportive evidence is lacking when compared to other surgical specialties. Multiple studies have demonstrated a 'real-world' benefit from the use of Knee arthroscopic ability on a cadaver knee in a simulated intra-operative environment using the validated Global Rating Scale, 49 arthroscopic checklist, and procedural time -for both diagnostic examination and probing examination; additionally, participants were given an untrained task (partial medial meniscectomy) to assess skill transfer, which was assessed using the same metrics as above VR-trained participants outperformed both lowfidelity trained and control groups when assessed with the GRS, for diagnostic examination, probe examination, and partial medial meniscectomy; no difference was observed between arthroscopic checklist completion between the VR and lowfidelity trained groups for the diagnostic and probe examinations, although both groups outperformed the untrained controls; 31% of participants were able to complete the partial meniscectomy vs 0% in the low-fidelity and control groups; VR-trained and low-fidelity groups showed significantly lower procedural times vs controls, but were not significantly different from each other.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46] It is in this area of transferability that supportive evidence is lacking when compared to other surgical specialties. Multiple studies have demonstrated a 'real-world' benefit from the use of Knee arthroscopic ability on a cadaver knee in a simulated intra-operative environment using the validated Global Rating Scale, 49 arthroscopic checklist, and procedural time -for both diagnostic examination and probing examination; additionally, participants were given an untrained task (partial medial meniscectomy) to assess skill transfer, which was assessed using the same metrics as above VR-trained participants outperformed both lowfidelity trained and control groups when assessed with the GRS, for diagnostic examination, probe examination, and partial medial meniscectomy; no difference was observed between arthroscopic checklist completion between the VR and lowfidelity trained groups for the diagnostic and probe examinations, although both groups outperformed the untrained controls; 31% of participants were able to complete the partial meniscectomy vs 0% in the low-fidelity and control groups; VR-trained and low-fidelity groups showed significantly lower procedural times vs controls, but were not significantly different from each other.…”
Section: Discussionmentioning
confidence: 99%
“…Improvement in arthroscopic dexterity has been measured by global rating scales and motion analysis, and significant correlation between virtual-reality and bench-top knee arthroscopy simulators has been measured. 12 The more basic and simple the simulator, the easier it would be to incorporate it into everyday training. 13 Another very important aspect of training is maintaining the skills achieved with simulation or any other form of skills development.…”
Section: Discussionmentioning
confidence: 99%
“…Objective assessment metrics for laparoscopic surgery skills training have been proposed by several researchers (Chang et al 2016;Cotin et al 2002;Kowalewski et al 2014;Maithel et al 2006;Retrosi et al 2015;Reiley et al 2011;Oropesa et al 2014;Ritter and Scott 2007). Some proposed to design a scoring system to classify trainees' proficiency of surgical movements (Reiley et al 2011;Oropesa et al 2014).…”
Section: Introductionmentioning
confidence: 99%